FOREIGN DIRECT INVESTMENT (FDI), KEBIJAKAN INDUSTRI, DAN MASALAH PENGANGGURAN: STUDI EMPIRIK DI INDONESIA - Syamsudin, Syamsudin; Setyawan, Anton A. (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2008)
Unemployment has become one of the major problems in Indonesia in the last eight years. SBY administration decides many economic policies in order to overcome the problem, but it seems not enough. However, the rate of foreign direct investment in Indonesia is increasing in the last three years. Macroeconomic indicators show that everything in its right track. This research analyzes the effects of FDI rate to employment rate in Indonesia. This research uses empirical data from ADB from 1983-2004. This research uses error correction model as a tool of analyses. The result shows that FDI rate does not have effect to employment rate. It means that FDI does not open job opportunity for many unemployer in Indonesia. In the end, this paper discusses the possibility of industrial policy in order to provide direction for government to develop Indonesiaâs industry.